Effect of extremely low-frequency magnetic fields on light-induced electric reactions in wheat. (31st December 2022) - Grinberg, Marina; Mudrilov, Maxim; Kozlova, Elizaveta; Sukhov, Vladimir; Sarafanov, Fedor; Evtushenko, Andrey; Ilin, Nikolay; Vodeneev, Vladimir; Price, Colin; Mareev, Evgeny
ABSTRACT: Magnetic field oscillations resulting from atmospheric events could have an effect on growth and development of plants and on the responsive reactions of plants to other environmental factors. In the current work, extremely low-frequency magnetic field (14.3 Hz) was shown to modulate light-induced electric reactions of wheat ( Triticum aestivum L.). Blue light-induced electric reaction in wheat leaf comprises depolarization and two waves of hyperpolarization resulting in an increase of the potential to a higher level compared to the dark one. Fluorescent and inhibitory analysis demonstrate a key role of calcium ions and calcium-dependent H + -ATPase of the plasma membrane in the development of the reaction. Activation of H + -ATPase by the increased calcium influx is suggested as a mechanism of the influence of magnetic field on light-induced electric reaction.